The avenging spirit: mapping an ambivalent spirituality in Zimbabwean literature in English - Mutekwa, Anias (Taylor & Francis (Routledge), 2016)
Spirit possession is a central trope in Zimbabwean literature, not only in English, but also in indigenous languages. This article looks at the avenging spirit as it is manifested in Zimbabwean literature in English from the colonial days to the present, and uses postcolonial theory and Lewis’s social deprivation theory in the exploration. It shows how this trope, under colonialism, is used to represent contesting power discourses that seek a stranglehold on the people. It goes on to show how the same trope is used to recover suppressed discourses, voices and narratives, and also becomes a metaphor for fissures in Zimbabwean society in the aftermath of the war of liberation and the unfulfilled promises of the same. Finally, it explores the avenging spirit as a traditional belief system that is central in the psyche of many of the Zimbabwean people and which society has to contend with in the contemporary set up. The article goes on to argue however, that belief in the ngozi represents traditional knowledge systems that can be used to deal with African problems.